2017
DOI: 10.17957/ijab/15.0242
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-induced Perturbations in Growth, Oxidative Defense System, Catalase Gene Expression and Fruit Quality in Tomato

Abstract: Cadmium (Cd) toxicity causes leaf chlorosis, growth inhibition, and disruption of photosynthetic machinery. A pot experiment was conducted to evaluate the changes in growth, physiochemical attributes and expression level of the catalase (Cat2) gene in two tomato cultivars (cv. Nagina; cv. Roma) under cadmium (Cd) stress. Plants were subjected to various concentrations of Cd in soil medium (0, 160, 320, 640 and 1280 μM Cd) in full strength Hoagland nutrient solution. Elevated Cd concentrations caused an apparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
(31 reference statements)
2
15
0
Order By: Relevance
“…The continuous plant development in Cd-containing soil validates previous reports that tomato is able to acclimate to longterm Cd exposure, reaching sexual maturity (Gratão et al, 2012;Hédiji et al, 2015;Hussain et al, 2017), producing fruits (Figure 11a), and maintaining yield (Figure 11c) despite some impacts on plant growth (Figures 1 and 2, Figure S1, Tables S3 and S6). Although the mechanism behind this plant ability is poorly understood, data from the current study suggest a relation with reduced Mg concentration in roots, the only macronutrient that was altered between Cd-stressed and control plants' vegetative organs (Figure 4a).…”
Section: Low Mg Status Is Associated With Plant Acclimatization To supporting
confidence: 87%
See 1 more Smart Citation
“…The continuous plant development in Cd-containing soil validates previous reports that tomato is able to acclimate to longterm Cd exposure, reaching sexual maturity (Gratão et al, 2012;Hédiji et al, 2015;Hussain et al, 2017), producing fruits (Figure 11a), and maintaining yield (Figure 11c) despite some impacts on plant growth (Figures 1 and 2, Figure S1, Tables S3 and S6). Although the mechanism behind this plant ability is poorly understood, data from the current study suggest a relation with reduced Mg concentration in roots, the only macronutrient that was altered between Cd-stressed and control plants' vegetative organs (Figure 4a).…”
Section: Low Mg Status Is Associated With Plant Acclimatization To supporting
confidence: 87%
“…Tomato (Solanum lycopersicum L.) consumption increases every year due to the fruit attractiveness (many colors, shapes, sizes, and flavors), multiple utilizations (from in natura consumption to processed sauces), and production of therapeutic compounds (Bergougnoux, 2014;FAOSTAT, 2016). However, tomato fruits are a potential pathway for cadmium (Cd) entrance into the food chain (Gratão et al, 2012;Hussain, Saeed, Khan, Javid, & Fatima, 2015;Hussain et al, 2017;Kumar, Edelstein, Cardarelli, Ferri, & Colla, 2015), hence affecting human health by triggering infertility (Alaee, Talaiekhozani, Rezaei, Alaee, & Yousefian, 2014), causing kidney and bone diseases, and increasing cancer risk (Järup & Åkesson, 2009;Nair, Degheselle, Smeets, Van Kerkhove, & Cuypers, 2013). The threshold for Cd concentration in vegetables is set at 0.05 mg/kg (Commission of the European Communities, 2014), but tomato fruits can contain almost twice this limit (Hussain et al, 2015), even when plants are grown in soil with Cd concentrations accepted by the CETESB (i.e., below 3.6 mg/kg, CETESB, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that Cd can cause adverse effects on some physiological and biochemical process such as photosynthesis, energy production, lipid metabolism and water relations, thereby leading to diminished plant biomass and economic yield (Sanita and Gabbrielli, 1999;Ali et al, 2011;Atta Ullah et al, 2016). The toxic effect of Cd on plants is partly related to the increase of reactive oxygen species (ROS) including superoxide radicals (O2• − ), hydrogen peroxide (H2O2) and hydroxyl radical (•OH) (Zhang et al, 2009;Gill and Tuteja, 2010;Hussain et al 2017). Plants affected by ROS are extremely harmful to proteins, lipids and nucleic acids and bring about their oxidation (Pandey et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Tomato (Solanum lycopersicum L.) consumption increases every year due to the fruit attractiveness (many colors, shapes, sizes and flavors), multiple utilizations (from in natura consumption to processed sauces), and production of therapeutic compounds . However, tomato fruits are a potential pathway for cadmium (Cd) entrance into the food chain Hussain et al, , 2017, hence affecting human health by triggering infertility , causing kidney and bone diseases, and increasing cancer risk . The threshold for Cd concentration in vegetables is set at 0.05 mg kg -1 (Commission of the European Communities, 2014), but tomato fruits can contain almost twice this limit , even when plants are grown in soil with Cd concentrations accepted by the CETESB (CETESB, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the amount of Cd translocated to the fruits is proportional to its concentration in the growth media Hussain et al, 2017). The problem arose due to anthropogenic activities that strongly increased metal content in arable lands, augmenting Cd concentrations that range from 0.01 to 0.8 mg kg -1 in natural areas and up to 1500 mg kg -1 in contaminated areas (Kabata-Pendias, 2011).…”
Section: Introductionmentioning
confidence: 99%